IMPLEMENTATION OF HUMAN CAPITAL MANAGEMENT IN THE DIGITAL TRANSFORMATION OF THE MANUFACTURING INDUSTRY - Hasibuan, Abdurrozzaq; Febrian, Muhammad Ade; Maryam, Tengku; Veronica, Nabila (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Digital transformation in the manufacturing industry has become a key factor in enhancing productivity and operational efficiency. One of the critical elements for successful digital transformation is effective Human Capital Management (HCM). This study aims to analyze the role of HCM in supporting digital transformation in the manufacturing industry. The research method used in this study is literature review, where various related sources on HCM and digital transformation are collected, analyzed, and compared to provide a comprehensive understanding of the relationship between the two. The results of the study indicate that the successful implementation of HCM can enhance employees' skills and performance, which in turn supports the adoption of new technologies in manufacturing companies. This study also identifies the challenges companies face in implementing HCM, such as resistance to change and digital skill gaps. In conclusion, manufacturing companies that effectively manage their human resources with appropriate HCM strategies can accelerate the digital transformation process and achieve a competitive advantage.